2011
DOI: 10.1086/658671
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Outbreaks of Nosocomial Infection with Influenza A/H3N2 Virus Variants

Abstract: This study showed the dissemination of highly homologous influenza virus variants among inpatients and HCWs within a short period, as a result of nosocomial transmission. These strains were also similar to influenza strains that were circulating in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Detection of respiratory viruses in symptomatic staff, including high-risk pathogens such as RSV, influenza, parainfluenza, and metapneumovirus, indicates multiple opportunities for staff to introduce community respiratory viruses into an outpatient clinic. All these respiratory viruses have been associated with inpatient nosocomial outbreaks and have the potential to cause severe disease in immunocompromised patients [31][32][33]. Strict policies restricting symptomatic staff from working may mitigate the potential impact of provider transmission as the source of nosocomial outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of respiratory viruses in symptomatic staff, including high-risk pathogens such as RSV, influenza, parainfluenza, and metapneumovirus, indicates multiple opportunities for staff to introduce community respiratory viruses into an outpatient clinic. All these respiratory viruses have been associated with inpatient nosocomial outbreaks and have the potential to cause severe disease in immunocompromised patients [31][32][33]. Strict policies restricting symptomatic staff from working may mitigate the potential impact of provider transmission as the source of nosocomial outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…These data were used to identify lapses in, and reaffirm the importance of stricter infection control measures. 29 Full length analyses of neuraminidase and haemagglutinin genes of influenza A(H1N1)pdm09 viruses during the 2011 influenza season showed that they were distinct compared to viruses that were circulating during the influenza pandemic of 2009, but associated with viruses collected from Newcastle, Australia, at the time of transmission of oseltamivir resistant A(H1N1)pdm09 viruses in the community. 26 Similar techniques have also identified the circulation patterns of influenza B viruses, an observation that assists with understanding influenza vaccine composition and effectiveness.…”
Section: Detection Of Antiviral Resistancementioning
confidence: 99%
“…Despite the existence of infection control policies and protocols, nosocomial transmission of respiratory viruses is a common problem that can occur in virtually any health-care setting [1][2][3][4][5][6][7]. The close proximity of patients, visitors and healthcare workers (HCWs) to one another, virus shedding during asymptomatic periods, low vaccination compliance (by both HCWs and the general public) as well as virus persistence in respiratory secretions and fomites can all contribute to the spread of the virus and lead to nosocomial outbreaks [2,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, influenza nosocomial transmission investigations have employed molecular techniques to corroborate comprehensive epidemiological data sets [4][5][6][7]34]. These studies through the sequencing of the Influenza hemagglutinin (HA) /neuraminidase (NA) and/or PB2 genomic regions, enabled researchers to determine virus isolate phylogenies and the potential epidemiological linkages between cases and HCWs.…”
Section: Introductionmentioning
confidence: 99%